Characterization of lactylation modification subtypes and the promoting role of CCL20 in hepatocellular carcinoma progression - Wu, Li-Hong; Yang, Liu; Wang, Xiang-Xu; Bai, Shuang; Yan, Xi; Wei, Jing; Wang, Jun; Tian, Fei (Frontiers in Genetics, 2025)
BackgroundHepatocellular carcinoma (HCC) is a highly aggressive and deadly malignancy. Early identification of prognostic risk factors is crucial for guiding clinical management and improving patient outcomes. Lactylation modification plays a pivotal role in tumorigenesis, yet the regulatory mechanisms and prognostic significance of lactylation-related genes in HCC remain insufficiently understood.MethodsThis study screened for prognostically significant lactylation modification-related genes based on their expression levels, integrated with DFS, PFS, and OS data. HCC patients were stratified into three distinct lactylation modification subtypes (C1, C2, C3) using the NMF algorithm. Differentially expressed genes across the three subtypes were identified through an intersection analysis. A lactylation modification-related prognostic model was subsequently constructed using LASSO-Cox and multivariate Cox regression analyses. The CIBERSORT algorithm was utilized to analyze immune cell infiltration. Functional validation of the lactylation-related gene CCL20 in HCC was conducted through in vitro experiments using HCC cell lines.ResultsWe identified three distinct lactylation modification patterns, with higher lactylation modification levels correlating with worse prognosis in HCC. A six-gene lactylation modification-based prognostic model (LRPS), including FAM83D, ENO1, PFN2, LCAT, PTGR1, and CCL20, was constructed and validated. Overall survival was markedly reduced in the high LRPS group relative to the low LRPS group. The high LRPS group also showed a significantly higher frequency of TP53 mutations. Correlation analysis of immune cell infiltration revealed a significant association between LRPS and the infiltration abundance of M0 macrophages, Tregs, and neutrophils, suggesting that lactylation modification may influence the tumor immune microenvironment. Overexpression of CCL20 in HCC cells significantly enhanced their proliferative and migratory capacities, indicating a key role for CCL20 in HCC progression.ConclusionThis study established a lactylation modification-based prognostic model that accurately forecasts outcomes in HCC patients. This risk score showed a significant correlation with glucose metabolism and reflected immune cell infiltration patterns. The core model gene, CCL20, promotes HCC cell proliferation and migration, supporting its potential as a valuable prognostic biomarker and a therapeutic target for HCC.